2020
DOI: 10.1016/j.earlhumdev.2020.105190
|View full text |Cite
|
Sign up to set email alerts
|

Maternal influences on fetal brain development: The role of nutrition, infection and stress, and the potential for intergenerational consequences

Abstract: An optimal early life environment is crucial for ensuring ideal neurodevelopmental outcomes. Brain development consists of a finely tuned series of spatially and temporally constrained events, which may be affected by exposure to a sub-optimal intra-uterine environment. Evidence suggests brain development may be particularly vulnerable to factors such as maternal nutrition, infection and stress during pregnancy. In this review, we discuss how maternal factors such as these can affect brain development and outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 120 publications
(120 reference statements)
1
49
0
1
Order By: Relevance
“…Similarly, early gestational exposure is most likely to be associated with adverse neurodevelopmental outcomes. [47][48][49] Given that only 25 maternal SARS-Cov-2 infections (8 imputed) in our sample occurred in the first trimester, our results provide limited power for detecting an association between infection at this early time point and neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, early gestational exposure is most likely to be associated with adverse neurodevelopmental outcomes. [47][48][49] Given that only 25 maternal SARS-Cov-2 infections (8 imputed) in our sample occurred in the first trimester, our results provide limited power for detecting an association between infection at this early time point and neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…participants experienced an asymptomatic or mild SARS-CoV-2 infection, and therefore, infants exposed to significant MIA may not be represented in our data. Similarly, early gestational exposure is most likely to be associated with adverse neurodevelopmental outcomes [46][47][48] . Given that only 21 maternal SARS-Cov-2 infections (8 imputed) in our sample occurred in the first trimester, our results provide limited power for detecting the effects of infection at this early timepoint.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that there is a relationship between intrauterine environmental factors affecting fetal nutrition and the development of obesity and chronic diseases later in adult life [ 2 ]. The Developmental Origins of Health and Disease (DOHaD) hypothesis assumes that the prenatal period is a sensitive developmental period in which exposure to adverse environments as malnutrition, infection, or stress can have long-term or lasting effects on the health path of the offspring—this is termed “developmental programming” [ 7 ]. The “thrifty phenotype” hypothesis has been further developed to suggest that developmental programming is only one of a series of adaptations that occur in an external environment predicted during development.…”
Section: Fetal Origin Hypothesismentioning
confidence: 99%